2016
DOI: 10.1080/13596748.2016.1195170
|View full text |Cite
|
Sign up to set email alerts
|

The influence of curriculum on master’s students’ perceived abilities in four domains of graduateness

Abstract: Potentially all university graduates, regardless of the discipline they have studied, are expected to have obtained generic learning outcomes, which we refer to as 'graduateness' . This study investigates the extent to which learning programmes' emphasis on graduateness affects students' perceived abilities in the domains of graduateness. Four domains of graduateness are considered: reflective thinking, scholarship, moral citizenship and lifelong learning. Based on curriculum maps, master's programmes were clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In literature, there are studies that associate lifelong learning competencies to undergraduate, graduate and doctorate programs in higher education (Griffin, 1982;Pepper, 2011;Pitman & Broomhall, 2009;Reeves, 2011). In the study called -The influence of curriculum on master's students' perceived abilities in four domains of graduateness‖ conducted by Steur, Jansen and Hofman (2016), it was found that there is no difference between the students who are enrolled in the programs that do not emphasize lifelong learning and those enrolled in the programs that emphasize lifelong learning. However, researchers suggest that program contents and practices should be examined more closely in terms of having lifelong learning competencies.…”
Section: Lifelong Learning and Higher Educationmentioning
confidence: 99%
“…In literature, there are studies that associate lifelong learning competencies to undergraduate, graduate and doctorate programs in higher education (Griffin, 1982;Pepper, 2011;Pitman & Broomhall, 2009;Reeves, 2011). In the study called -The influence of curriculum on master's students' perceived abilities in four domains of graduateness‖ conducted by Steur, Jansen and Hofman (2016), it was found that there is no difference between the students who are enrolled in the programs that do not emphasize lifelong learning and those enrolled in the programs that emphasize lifelong learning. However, researchers suggest that program contents and practices should be examined more closely in terms of having lifelong learning competencies.…”
Section: Lifelong Learning and Higher Educationmentioning
confidence: 99%